2004
DOI: 10.1002/bdd.404
|View full text |Cite
|
Sign up to set email alerts
|

DM27, an enaminone, modifies the in vitro transport of antiviral therapeutic agents

Abstract: DM27, an enaminone, increased the transport of antiretroviral drugs and acyclovir in a nontoxic manner without affecting the paracellular or transcellular transport of these drugs. This study suggests that DM27 may be used as a P-gp efflux inhibitor to enhance the oral bioavailability of antiviral drugs and that drug-drug interactions will most probably be encountered upon co-administration of P-gp substrate drugs with enaminones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…A permeability study employing 3H‐aciclovir indicated an apparent permeability coefficient of about 1.19 × 10 −5 cm/s,53 but other reports obtained considerably lower values, ranging from of 0.12 × 10 −6 44 to 2.0 × 10 −6 cm/s,54 see Table 3. As drugs with a permeability in the range 70–100% absorbed usually have a P app value greater than 10 × 10 −6 cm/s,54 most of these data suggest that permeability of aciclovir is low.…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 97%
“…A permeability study employing 3H‐aciclovir indicated an apparent permeability coefficient of about 1.19 × 10 −5 cm/s,53 but other reports obtained considerably lower values, ranging from of 0.12 × 10 −6 44 to 2.0 × 10 −6 cm/s,54 see Table 3. As drugs with a permeability in the range 70–100% absorbed usually have a P app value greater than 10 × 10 −6 cm/s,54 most of these data suggest that permeability of aciclovir is low.…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 97%
“…9,10 In addition, they serve as a basic synthon for various pharmaceutical drug molecules that control physiological actions, such as anti-bacterial, 11,12 anticonvulsant, 13 antitussive, 14 anti-inammatory, 15 anti-tumor drugs. These chemicals are a highly multifaceted class of intermediates for the synthesis of heterocyclic and biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 37h caused a statistically significant increase (139.2%) in cyclosporin A (CSA, a P‐gp substrate and inhibitor) transport at 10 −7 M. Since 37h proved a more potent P‐gp inhibitor than 37i , the transport of antiviral P‐gp substrates (zidovudine, saquinavir, ritonavir, amprenavir, and acyclovir) was evaluated in Caco‐2 cells and was shown to be significantly ( P < 0.05) enhanced over a range of 23.7–51.3% after 37h coincubation. The P app values for acyclovir, saquinavir, amprenavir, ritonavir, and zidovudine were statistically higher in the 37h treated group compared to the control group with ∼25%, 23.7%, 44.7%, 51.3%, and 29.4% increases, respectively 176. The effect of 37h on the transport of acyclovir and the antiretroviral agents reflected the relative differences in their efflux properties and P‐gp affinity in reference to 37h , where zidovudine (substrate for multiple transporters such as P‐gp, MRP, OATP and OAT, and nucleoside systems)177, 178 displayed maximal 37h ‐effect at 10 −4 M, while ritonavir (high affinity P‐gp substrate) displayed maximal 37h ‐effect at 10 −10 M. …”
Section: The Enaminones As Potential P‐gp Inhibitorsmentioning
confidence: 88%
“…Comparing 37h inhibitory effect to other P‐gp inhibitors revealed that 37h was more potent in increasing paclitaxel apical to basolateral transport [360% vs. 212.6% with 37h ( 10 −6 M) and CSA (5 × 10 −6 M), respectively] of 3.22, 2.18, and 2.48, respectively. Additionally, the unaltered transport of mannitol (paracellular marker) and propranolol (transcellular marker) suggest that the effect of 37h on paclitaxel transport was through P‐gp modulation rather than modulation to the paracellular or the transcellular routes, respectively 176…”
Section: The Enaminones As Potential P‐gp Inhibitorsmentioning
confidence: 99%